MDE-S: A case study of the Health Company Diagnostic Method applied in three health units (Revista do LabDGE - UFF, 2023)
The objective of this study was to evaluate the degree of organizational maturity in three Emergency Care Units (a.k.a. UPA in Brazilian acronym) in a city in the interior of the state of São Paulo - Brazil, with the following fundamental criteria observed: the utility, feasibility, and specialized technical knowledge of the health unit contextualized in this study. The method used was the Health Company Diagnostic Method (MDE-S), which is an approach to study and qualify the level and organizational maturity, that has the fundamental characteristic of providing a cycle of continuous improvement in the company. Among the most relevant results, the study demonstrated, in comparison with a study conducted in Basic Health Units in the interior of the state of Rio de Janeiro, an existent lack of knowledge in health management tools and basic administration fundamentals of the evaluated units. Finally, the study recommends that a strategic system be created for the management and deployment of goals and guidelines, based on Hoshin Kanri. It is considered that, despite the challenges that will certainly occur, this small-scale and well-developed diagnostic system will certainly be useful and may become an important step towards a continuous practice of efficient management in the investigated health unit.